2016
DOI: 10.1016/j.molonc.2016.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy inhibition upregulates CD4+ tumor infiltrating lymphocyte expression via miR‐155 regulation and TRAIL activation

Abstract: A B S T R A C TChemoresistance is a major challenge in lung cancer treatment. Recent findings have revealed that autophagic mechanism contributes significantly to immunosuppressive related chemoresistance. For that reason, targeting autophagy-related immunosuppression is an important approach to reverse tumor drug resistance. In this study, we report for the first time that autophagy inhibition triggers upregulation of CD4 þ , Foxp3 þ tumor infiltrating lymphocytes in late metastatic lung cancer tissues. Furth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(30 citation statements)
references
References 51 publications
1
29
0
Order By: Relevance
“…Of note, recent findings have revealed that autophagy contributes to immunosuppressive-related chemoresistance and promotes the capability of the tumor to avoid immune detection [83, 84]. Along the same line, enhanced autophagy has been observed in advanced stages of metastatic diseases, characterized by low levels of tumor-infiltrating T lymphocytes (TILs) [85]. Although this area of research is still poorly explored, autophagy could be considered a critical process for counteracting CSCs resistance to immunotherapeutic approaches.…”
Section: Autophagy and Cancer Stem Cellsmentioning
confidence: 99%
“…Of note, recent findings have revealed that autophagy contributes to immunosuppressive-related chemoresistance and promotes the capability of the tumor to avoid immune detection [83, 84]. Along the same line, enhanced autophagy has been observed in advanced stages of metastatic diseases, characterized by low levels of tumor-infiltrating T lymphocytes (TILs) [85]. Although this area of research is still poorly explored, autophagy could be considered a critical process for counteracting CSCs resistance to immunotherapeutic approaches.…”
Section: Autophagy and Cancer Stem Cellsmentioning
confidence: 99%
“…2a-c) These data suggest that autophagy plays a role as a negative regulator of in ammation by regulating the expression of in ammatory cytokines.MiR-155 Is Involved in the Cytokine Production of DCs Induced by Dysfunctional AutophagyEarlier we showed that the expression of miR-155 was decreased in DCs from active BD patients [8]. Moreover, miR-155 has been reported to be involved in autophagy regulation [17,[25][26][27]. A further experiment was carried out to investigate if miR-155 was associated with cytokine production by DCs induced by dysfunctional autophagy.…”
mentioning
confidence: 81%
“…Thus, an EMT regulatory program for the exhaustion of CD8p tumor-infiltrating lymphocytes and immunosuppression of PD-L1 via the miR-200/ZEB1 axis is critical to tumor metastasis. Likewise, miR-155 functions as an immune system activator by blocking autophagy, which promotes the upregulation of CD4+ and infiltration of FoxP3+ tumor-infiltrating lymphocytes, which results in increased lung carcinoma chemosensitivity [ 41 ].…”
Section: Correlation Among Smoking Cancer and Expression Of Mirnmentioning
confidence: 99%